PENGARUH LOVE OF MONEY, OTORITAS ATASAN, IDEALISME, DAN RELATIVISME TERHADAP ETIKA PROFESI AKUNTAN - Indrayana, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The accountant profession is required not only to rely on special abilities and expertise but must have a character, namely ethics. The ethics of the accounting profession is needed so that what accountants do does not violate ethics. The purpose of this study was to explain and predict the effect of love of money, superior authority to cheat, idealism and relativism on the attitudes of accounting students regarding the ethics of the accounting profession. The theory of attitude and behavior as the basis used in this study to explain the influence of love of money, superior authority to cheat, idealism and relativism on the attitudes of accounting students regarding the ethics of the accounting profession. The number of samples used in this study were 140 respondents with the method of determining the sample, namely the simple random sampling method. Data was collected by using a questionnaire method. The analysis technique used is multiple linear regression analysis. The results of the analysis indicate that idealism has a positive effect on the attitudes of accounting students regarding the ethics of the accounting profession, while love of money, superior authority to cheat, and relativism have no effect on the attitudes of accounting students regarding the ethics of the accounting profession.